Ownership structure, corporate governance and corporate performance in Malaysia - Mohd Ghazali, Nazli Anum (Emerald Group Publishing Limited, 2010)
Purpose – Following the 1997 Asian financial crisis, the Malaysian Government introduced new regulations on corporate governance, recognizing the importance of restoring market confidence. The purpose of this paper is to evaluate the impact of the implementation of these new regulations on corporate performance